2016
DOI: 10.1016/j.neuropsychologia.2016.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Cathodal transcranial direct current stimulation over posterior parietal cortex enhances distinct aspects of visual working memory

Abstract: In this study, we investigated the effects of tDCS over the posterior parietal cortex (PPC) during a visual working memory (WM) task, which probes different sources of response error underlying the precision of WM recall. In two separate experiments, we demonstrated that tDCS enhanced WM precision when applied bilaterally over the PPC, independent of electrode configuration. In a third experiment, we demonstrated with unilateral electrode configuration over the right PPC, that only cathodal tDCS enhanced WM pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 41 publications
6
26
1
Order By: Relevance
“…For example, a number of studies also suggest a selective tDCS benefit among low-baseline populations, both within the WM domain (Gozenman & Berryhill, 2016;Heinen et al, 2016;Minichino et al, 2015;Tseng et al, 2012) as well as in other cognitive domains, such as attention and dual tasking (Reinhart et al, 2016;London & Slagter, 2015;Zhou et al, 2015). However, one critical difference between these studies and ours is that ours is a training study involving multiple sessions of stimulation in conjunction with task performance, rather than only a single session (but see also Looi et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…For example, a number of studies also suggest a selective tDCS benefit among low-baseline populations, both within the WM domain (Gozenman & Berryhill, 2016;Heinen et al, 2016;Minichino et al, 2015;Tseng et al, 2012) as well as in other cognitive domains, such as attention and dual tasking (Reinhart et al, 2016;London & Slagter, 2015;Zhou et al, 2015). However, one critical difference between these studies and ours is that ours is a training study involving multiple sessions of stimulation in conjunction with task performance, rather than only a single session (but see also Looi et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Several studies have demonstrated selective tDCS benefits among individuals with low, but not high, baseline WM abilities (Gozenman & Berryhill, 2016;Heinen et al, 2016;Tseng et al, 2012), and meta-analyses tend to report stronger effect sizes in clinical or older adult populations compared with the higher-performing young adult population (Dedoncker, Brunoni, Baeken, & Vanderhasselt, 2016;Hill, Fitzgerald, & Hoy, 2016;Hsu, Ku, Zanto, & Gazzaley, 2015;Summers, Kang, & Cauraugh, 2015). Moreover, the evidence extends beyond the WM domain.…”
Section: Baseline Performance and Other Individual Difference Factorsmentioning
confidence: 99%
“…More importantly, they also found that the tDCS effect varied with participants’ baseline digit span performance: only the high WM capacity group enjoyed an improvement after stimulation but not the low WM capacity group. Recently, Heinen et al (2016) also provided another evidence of tDCS effect varying with participants’ baseline performance. They showed that only cathodal stimulation enhanced WM precision, especially for those participants whose baseline performance was low.…”
Section: Introductionmentioning
confidence: 95%
“…Given the growing number of studies reporting varied effects of tDCS with different baseline performances (Gözenman and Berryhill, 2016; Heinen et al, 2016; Looi et al, 2016), it is important for studies to choose an appropriate baseline on which to evaluate the effect of tDCS. The studies mentioned above have mostly adopted participants’ behavioral performances from the sham condition to serve as a baseline to split the participants into different groups (Tseng et al, 2012, 2016; Hsu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to examine whether indeed the dorsal and ventral parts of the LPPC have different roles in episodic memory retrieval and the cognitive operations subserved by these regions. In addition, it has been shown that the tDCS exerts its effects to brain regions that are functionally connected to the stimulated area (e.g., Heinen, Sagliano, Candini, Husain, Cappelletti, & Zokaei, 2016;Liang et al 2014;Yu, Tseng, Hung, Wu, & Juan, 2015). The LPPC, together with the hippocampus, the parahippocampal cortex, the medial prefrontal cortex, and the retrosplenial/posterior cingulate cortex have been thought to form the "core recollection network" (King, de Chastelaine, Elward, Wang, & Rugg, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%